Current Concepts in Diagnosis and Treatment of Traumatic Brain Injury: Implications for Healthcare in Nepal - Sakowitz, Oliver W.; Sharma, Mohan R.; Kiening, Karl L. (Nepal Journal of Neuroscience, 2005)
Taumatic brain injury (TBI) is a leading cause of disability and death in the industrialized and in the developing world. With an incidence of 200-400 cases per 100.000, head injuries are a major contributor to socio-economic costs. The 20% suffering from severe head injury (SHI) requiring prolonged intensive care and/or neurosurgical intervention are of particular interest to specialist practitioners from multiple disciplines.This review covers the current concepts of diagnosis and treatment in these patients in the Western world, i.e. mainly the US and Western Europe. Special emphasis is laid upon evidence-based guidelines established during the last decade. Comparison is drawn to the current status of trauma care in Nepal.Management strategies for TBI can not be applied to Nepalese healthcare entirely. Effective management of head injured persons in Nepal is affected by its difficult geographical location, unavailability of trained personnel in the field, and difficulty in transporting the patients due to the lack of motorable roads. While some of the equipment for the treatment of TBI victims is readily available (e.g. ventricular drainage), others are scarce (e.g. operating room capacity, intensive care facilities) or completely unavailable (e.g. emergency medical service providers, specialized monitoring equipment). Realistic proposals for improvement of the current situation are made. Nepal Journal of Neuroscience, Volume 2, Number 1, 2005, page: 29-51